Dred Scott and the Problem of Constitutional Evil - Graber, Mark A (Cambridge University Press, 2013)
Constitutionalism, in this work, mediates the controversies that arise among citizens who hold clashing political aspirations. In regimes wracked with problems of constitutional evil, political actors must negotiate and renegotiate constitutional meanings with rivals whose positions they find morally abhorrent. The challenge of creating and preserving political relationships among people who hold conflicting conceptions of justice requires that compromises be forged in every dimension of political life